STATUS GIZI PADA IBU HAMIL SEBAGAI FAKTOR RISIKO KEJADIAN BERAT BAYI LAHIR RENDAH (STUDI DI KECAMATAN BANDUNG KABUPATEN TULUNGAGUNG) - Sentha Kusuma PJ; Martha Irene Kartasurya; Apoina Kartini (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Infants with low birth weight (LBW) had 35 times higher risk of death compared to infants of normal birth weight (NBW). Genesis Babies With Low Birth Weight (LBW) were associated to maternal age, height, birth space, parity, Chronic Energy Deficiency (CED) and anemia. This study aimed to prove that the nutritional status of pregnant women was a risk factor for low birth weight infants in Bandung District of Tulungagung. This research is an analytic observational case-control design using a retrospective approach. Subjects were 39 cases of mothers who delivered LBW babies and 78 control mothers who delivered NBW babies. Data hemoglobin levels and mid upper arm circumference of the mother were gathered from the mother's health books (book of MCH). Data on energy sufficiency level, protein adequacy level, and iron intake were obtained from the Food Frequency Questionnaire (FFQ). Data analyzed by chi square test. The results of this study concluded that anemia (OR = 4.4 95% CI 1.36 to 14.28), upper arm circumference <23.5 cm (OR = 4.2 95% CI 1.38 to 12.55), iron intake (OR = 3.5: 95% CI 1.51 to 7.99), protein adequacy level (OR = 3.4 95% CI 1.45 to 7.83), energy sufficiency level (OR = 3.2 95% CI 1.31 to 7.64), and the observance of iron tablet consumption (OR = 3.0: 1.09 to 8.49), are risk factors for the incidence of low birth weight (LBW ). And from the results, the average for mid upper arm circumference 23.7 cm ± 0.81, while the average hemoglobin level of 11, 7 g/dl ± 1.115. It is concluded that the arm circumference <23.5 cm and anemia in trimester three strongest risk factors of LBW.